Molecular characterization of a 42 kDa subunit pili protein of Salmonella typhi causes typhoid fever (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Darmawati S, Ethica SN, Prastiyanto ME, Depamede SN, Putri EO, Kamaruddin M. 2022. Molecular characterization of a 42 kDa subunit pili protein of Salmonella typhi causes typhoid fever. Biodiversitas 23: 962-968. Blood culture is the gold standard for diagnosing typhoid fever, but it has limitations such as media and laboratory equipment, specimen volume, and examination time. However, the Academy of Pediatrics does not recommend serology due to its low sensitivity.The purpose of this study was to determine the molecular properties of the protein pilli of Salmonella typhi(S. typhi) that the findings can be used to develop a typhoid fever diagnostic reagent. The SDS-PAGE method was used, as well sequence analysis with ProtParam, ProtScale, and PSIPRED. The SDS-PAGE profile reveals one major protein (42 kDa) and fourteen minor proteins. The pili protein subunit 42 kDa had an amino acid (AA) sequence with a length of 390 AA, according to bioinformatics analysis. According to the ProtParam results, the pili protein subunit 42 kDa has good stability with a value of 40 and is a hydrophilic protein with an average GRAVY value of -0.950. PSIPRED results show that among the secondary structural elements, coil strand predominates, followed by -helix and -strand. It is concluded that this protein is immunogenic and that it can be used to develop a more specific and sensitive diagnostic reagent for typhoid fever.